2019
DOI: 10.4103/jfmpc.jfmpc_660_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of short sleep duration and effect of co-morbid medical conditions – A cross-sectional study in Saudi Arabia

Abstract: Background:Sleep is crucial to human's health and essential for a person's wellbeing. It is involved in multiple physiological mechanisms, such as metabolism, appetite regulation, immune and hormone function, and cardiovascular systems. The National Sleep Foundation recommends 7–9 h of sleep each night for adults. Short (<7 h) and long (<9 h) sleep duration has been reported to be associated with increased risk of morbidity and mortality.Aim:1) To assess the prevalence of short sleep durations among Saudi adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
7
0
2
Order By: Relevance
“…Sleep assessment indicated that about half of our participants achieved the recommended sleep duration [ 47 ]. This prevalence was similar to previously reported levels in studies conducted prior to COVID-19 [ 48 , 49 ]. However, about 58% of our sample reported poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…Sleep assessment indicated that about half of our participants achieved the recommended sleep duration [ 47 ]. This prevalence was similar to previously reported levels in studies conducted prior to COVID-19 [ 48 , 49 ]. However, about 58% of our sample reported poor sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…Descriptive synthesis. Ten articles [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] were included in the final sample ( Table 1 ). They were all cross-sectional studies and published between 2006 and 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Em outra perspectiva, a pesquisa de Althakafi et al (2019) sugere que a diminuição na duração do sono poderia resultar em maior resistência à insulina, concomitante à queda do hormônio que suprime a ingesta alimentar denominado leptina e aumento do hormônio estimulante da fome, a grelina, o que ocorre por intermédio da regulação do eixo hipotálamoadrenal. Essa associação estaria envolvida com o surgimento de anormalidades metabólicas e aumento do peso.…”
Section: Conforme O Estudo Deunclassified
“…Ainda de acordo comAlthakafi et al (2019), há uma estreita ligação entre a breve duração de sono e maiores chances de desencadear hiperlipidemias, acidentes automobilísticos e doenças arteriais coronarianas. Dados desse mesmo estudo afirmam a existência de uma associação entre o aumento da idade e a curta duração do sono, visto que, dentre os pesquisados, os participantes com idade superior a 30 anos dormiam menos do que 7 horas diárias de sono.…”
unclassified